Analisis Penyerangan Jepang ke Palembang dan Pertempuran Laut Jawa Ditinjau dari Aspek Strategi serta Manfaatnya bagi TNI Angkatan Laut - Jasmin Murdianto; Fadelan Fadelan; Mochamad Achnaf (UJoST- Universal Journal of Science and Technology, 2023)
An economic embargo imposed by the US, Netherlands and Britain on Japan has forced the country to seek natural resources (petroleum) in Southeast Asia to sustain its war needs. This reason then motivated Japan to attack and control natural resources on the island of Sumatra and Java. The Japanese invasion of Palembang for control of the Allied oil refinery at Plaju and the battle of the Java Sea were evidence of Japan's ambition to control Indonesia's natural wealth. This research uses a qualitative method approach with a type of literature study research. Data collection comes from literature studies in the form of books, journals and other sources of information. The benefit that can be taken from this battle analysis is that natural resources and energy are attractions that can trigger